Supply Chain Finance by Development Banks and Public Entities - International Finance Corporation (World Bank Group, Washington, DC, 2021)
For many small and medium enterprises (SMEs), access to financing is a challenge. The World Bank Group estimates the finance gap among formal micro, small, and medium enterprises (MSMEs) in developing economies to be eighteen percent of GDP. This finance gap is of particular concern because SMEs are a leading driver of trade, economic development, and employment. Development finance institutions can play an active role by fostering initiatives, such as supply chain finance (SCF), that can for instance, drive local economic growth, increase financial inclusion, and support the closing of market gaps. This guidebook deals with development banks on a national and multinational level. Similarly, some of the discussed goals and roles can also apply to central banks, government agencies, or other public entities.